The Influence of Corporate Social Responsibility and Company Life Cycle on Firm Value in Manufacturing Companies listed on the Indonesia Stock Exchange - Muhammad Razif; Dina Patrisia (Financial Management Studies, 2023)
This study aims to analyze whether there is an effect of corporate social responsibility and life cycle on firm value. The object of this research is a manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2018-2019. The sample selection in this study used a purposive sampling method and the data used were secondary data. The sample in this study was 79. The analytical technique used for this study was multiple linear regression analysis. Data processing using SPSS application. The result of this research is that corporate social responsibility has a negative effect on firm value with a significance of 0.010. The company's life cycle has no effect on the value of the company with a significance value of 0.447.